The Effect of Relational Embeddedness, Absorptive Capacity, and Learning Orientation on SMEs’ Competitive Advantage - Guo-Song Wu; Michael Yao-Ping Peng; Michael Yao-Ping Peng; Zhong Chen; Zongmin Du; Muhammad Khalid Anser; Wen-Xuan Zhao (Frontiers in Psychology, 2020)
The combination of external new knowledge and organizational capability has become a cornerstone in the internationalized enterprises. Sources of knowledge acquisition are among the most valuable resources that an internationalized firm can achieve competitive advantage. This study aims to explore this phenomenon between knowledge sources and competitive advantage in the context of internationalized small and medium enterprises (SMEs) mainly by a quantitative approach. Based on contextual nature of resource–capability–competitive, absorptive capacity has long been a critical construct in organizational studies, as well as referring relational embeddedness as potential drivers of absorptive capacity, which is moderated by learning orientation. This study also investigates the mediating effect of absorptive capacity in terms of knowledge absorption and integration on international competitive advantage. To gain insights and provide essential implications for internationalized SMEs from the global economy, this study adopted purposive sampling to collect 211 valid responses. Via the partial least-squares structural modeling, the relationships among relational embeddedness, potential and realized absorptive capacity, and competitive advantage were measured. The results suggest that relational embeddedness positively influences potential and realized absorptive capacity with moderating effect of learning orientation. Potential and realized absorptive capacities have full mediating effect between relational embeddedness and competitive advantage. This study concludes insights and implications for research and practice.